Education on the Wise Use of Artificial Intelligence (AI) to Improve Digital Literacy and Promote Innovation and Self-Reliance Among Students and the Public in Indonesia and Thailand - Wiwik Pudjaningsih; Nur Intan Rochmawati; Lisa Virdinarti Putra; Sisca Septiani; Ridwan Ali; Prattana Srisuk; Marlon Rael Astillero; Nico Irawan (Jurnal Pengabdian Masyarakat Bestari, 2026)
The digital literacy gap in Indonesia and Thailand underscores the need for education on the wise use of artificial intelligence (AI) for students and the general public. This community service activity was conducted online via the Zoom platform, involving participants from both countries. The objective of the activity was to enhance participants’ understanding of AI concepts, benefits, risks, and how to use it ethically and responsibly in the context of education and daily life. The methods used included interactive lectures, discussions, and Q&A sessions with international speakers. The results of the activity showed an increase in participants’ understanding of AI-based digital literacy as well as a growing motivation to innovate independently. This activity contributed to strengthening students’ digital competencies in line with Indonesia’s Society 5.0 agenda and Thailand’s Education 4.0 agenda.